Silvanella coronata Dragastan (Bryopsidophyceae, Family Pseudoudoteaceae) from late Jurassic of Carpathians carbonate platforms (Romania) - Dragastan, Ovidiu (HIDROBIOLÓGICA, 2017)
A new calcareous green alga Silvanella coronata Dragastan (Bryopsidophyceae, Pseudoudoteaceae) was discovered in the Late Jurassic deposits of Getic Carbonate Platform (Carpathians). The taxon and the name of genus are dedicated to Dr. Paul C. Silva, University of California at Berkeley, in occasion of his 80th anniversary.